Ensuring safe disposal: hospital preparedness for managing medical waste during the COVID-19 pandemic - Lestari, Selfi Octaviani; Zakianis; Sapta, Wibowo Ady (BKM Public Health and Community Medicine, 2023)
Purpose: The increasing volume of medical waste generated during the COVID-19 pandemic poses a significant challenge to hospitals, highlighting the urgent need for effective hospital waste management. However, the current medical waste management practices in many hospitals may not be sufficient to handle the surge in waste, highlighting a critical gap in the system. This study. The present study aims to review articles discussing problems and solutions in low- and middle-income countries (LMICs) related to hospital waste management during the COVID-19 pandemic. Methods: This review study was performed by searching four databases - Scopus, Science Direct, PubMed, and ProQuest from 2020-2022. Results: Based on the findings of the article review, the 3R process - Reduce, Reuse, and Recycle - proves crucial in managing medical waste, particularly during the COVID-19 pandemic. This process serves as the primary stage in medical waste management, effectively minimizing the burden on the subsequent stages, such as storage, transportation, and final processing. By implementing the 3R process, healthcare facilities can effectively reduce the volume of medical waste, consequently mitigating the negative impact of the pandemic on the environment. Therefore, it is essential to prioritize the 3R process in managing medical waste to address the increasing generation of medical waste brought about by the COVID-19 pandemic. Conclusion: The COVID-19 pandemic has highlighted the need for stronger management and law enforcement commitment in LMIC hospitals. These events require hospitals to be better prepared for emergencies like pandemics. Therefore, governments and healthcare institutions must prioritize emergency preparedness measures to effectively handle such crises. By taking proactive measures to improve hospital management and law enforcement, LMICs can be better equipped to manage future pandemics and protect the health of their citizens.